2019
DOI: 10.1155/2019/5945178
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Initial and Sustained Remission in Patients Treated with Antithyroid Drugs for Graves’ Hyperthyroidism: The RISG Study

Abstract: Purpose. To study predictors of attaining (part 1) and sustaining (part 2) remission in patients with Graves' hyperthyroidism (GH) treated with antithyroid drugs (ATD). Methods. In the prospective first part, the included patients were treated with ATD until a prespecified definition of remission (thyrotropin > 0.4 mU/L and TSH-receptor antibodies (TRAb) ≤ 1. 0 IU/L in a patient receiving a methimazole dose ≤ 5 mg/day, on two occasions two months apart) was met, or for 24 months. In the second part, patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Previous studies by Karmisholt et al and Vos et al has been conducted in order to predict recurrence in GD patients [ 12 , 21 ]. The Remission Induction and Sustenance in Graves’ Disease (RISG) study in Denmark found that only TRAb measured in the time of diagnosis of GD has the superiority as prognostic marker for GD remission [ 21 ]. Other study in the Netherlands successfully created GREAT Score for predicting recurrence in GD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies by Karmisholt et al and Vos et al has been conducted in order to predict recurrence in GD patients [ 12 , 21 ]. The Remission Induction and Sustenance in Graves’ Disease (RISG) study in Denmark found that only TRAb measured in the time of diagnosis of GD has the superiority as prognostic marker for GD remission [ 21 ]. Other study in the Netherlands successfully created GREAT Score for predicting recurrence in GD.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been done to identify factors influencing the recurrence of GD, such as age, gender, thyroid size, antithyroid dosage, smoking history, thyroid echogenicity, thyroid volume, serum TSH level, thyrotropin receptor antibody (TRAb), and thyroxin peroxidase antibody (TPO-Ab) [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. A meta-analysis of pre-treatment GD patients found some significant risk factors associated with disease recurrence following ATD withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…10,11,15,17,21,22,[24][25][26] In the 'Remission induction and sustenance in Graves' disease' (RISG) study, the rate of remisson was found to be 63% in patients with baseline TRab levels below 10 IU/l instead of 39% above 10 IU/l. 27 Quadbeck et al showed that when the cut-off value for TRab was taken as 1.5 IU/l or 10 IU/l, TRab had positive predictive value of 49% or 83%, negative predictive value of 54% or 62%, and specificity of 14% or 92%. 17 We took the cut-off value for TRab as 10 IU/l and we observed in newly-diagnosed patients that the time to become euthyroid was shorter with TRab<10IU/l compared to the TRab levels ≥10IU/l.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid-stimulating antibodies can be used in GD for many objectives, such as diagnosis (4), as well as during follow-ups to predict which patients will relapse after stopping ATD (4,(9)(10)(11)(12)(13)(14). They also have important values in assessing the risks of developing GO (12) and fetal/neonatal hyperthyroidism (15,16).…”
Section: Contextmentioning
confidence: 99%
“…The use of ATD is accompanied by a series of markers demonstrating immune system restoration, such as decreased HLA in thyroid cells (17), and decreased markers of inflammation, such as Interleucines 1, 5, and 6 and tumor necrosis factor-alpha (18,19). There are also increases in T cell suppressors, decreases in T helper cells (20), and decreases in TRAb values over time (9,10,(21)(22)(23)(24).…”
Section: Serum Trab During Atd Therapymentioning
confidence: 99%